2012
DOI: 10.1111/j.1600-0501.2011.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and postoperative assessment of sinus grafting procedures using cone‐beam computed tomography compared with panoramic radiographs

Abstract: A preoperative planning based on CBCT seems to improve sinus diagnostics and surgical confidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 25 publications
2
31
0
1
Order By: Relevance
“…However, additional surgically relevant information had no impact at all on surgical procedures (augmentation, implant length). Similarly, a concordance between planning from CBCT and from panoramic radiography of nearly 95% was reported (Baciut et al, 2013). In addition, it was pointed out in a recent study that planning of augmentation requirements based on 2-or 3-dimensional images was, in the majority of the cases, in agreement with the actual surgical procedure (Dagassan-Berndt et al, 2015).…”
Section: Discussionmentioning
confidence: 51%
“…However, additional surgically relevant information had no impact at all on surgical procedures (augmentation, implant length). Similarly, a concordance between planning from CBCT and from panoramic radiography of nearly 95% was reported (Baciut et al, 2013). In addition, it was pointed out in a recent study that planning of augmentation requirements based on 2-or 3-dimensional images was, in the majority of the cases, in agreement with the actual surgical procedure (Dagassan-Berndt et al, 2015).…”
Section: Discussionmentioning
confidence: 51%
“…Thus, the accuracy of identifying alveolar bone borders on radiographs and CBCT scans may be overestimated. Baciut et al [7] stated that when only panoramic radiography is used to assess alveolar bone, there is a risk of overestimating the quality and quantity of the bone. Our findings were in accordance with those of Baciut et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…Baciut et al [7] stated that when only panoramic radiography is used to assess alveolar bone, there is a risk of overestimating the quality and quantity of the bone. Our findings were in accordance with those of Baciut et al [7]. We showed that, compared with CBCT and direct measurements, panoramic radiography overestimated bone loss in both extraction socket dimensions and alveolar bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computed tomography and three-dimensional imagingassist the oral surgeon in determining the individual anatomical structuresshape and volume, and evaluating the changes in the graftvolume loss over time with high accuracy. [4,5] Baciut M. et al [6]performed a pre-and postoperative assessment of the maxillary sinuses on 13 patients (16 sinuses)witha planned sinus augmentation procedure, using panoramic radiographs (OPG) and CBCT scans. The study comprised choice of treatment, timing of implant placement, sinus morphology, complication prediction and graft volume assessment.A preoperative planning based on CBCT provides better diagnostics and a more precise postoperative monitoring.…”
Section: Introductionmentioning
confidence: 99%